2010
DOI: 10.1073/pnas.0910945107
|View full text |Cite
|
Sign up to set email alerts
|

Sexual isolation of male moths explained by a single pheromone response QTL containing four receptor genes

Abstract: Long distance sexual communication in moths has fascinated biologists because of the complex, precise female pheromone signals and the extreme sensitivity of males to specific pheromone molecules. Progress has been made in identifying some genes involved in female pheromone production and in male response. However, we have lacked information on the genetic changes involved in evolutionary diversification of these mate-finding mechanisms that is critical to understanding speciation in moths and other taxa. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 58 publications
4
93
0
1
Order By: Relevance
“…In strong support of this idea, Gould et al (14) showed that a cluster of OR genes expressed in the antenna is very tightly linked to an autosomal gene controlling the interspecific difference in male behavioral response among Heliothis virescens and Heliothis subflexa. Moreover, single-cell recordings showed that species-specific spike-amplitude responses to individual pheromone components were also linked to the OR cluster (14). In O. nubilalis, five of the seven pheromone ORs are located within a large cluster on the Z chromosome (34).…”
Section: Significancementioning
confidence: 81%
See 2 more Smart Citations
“…In strong support of this idea, Gould et al (14) showed that a cluster of OR genes expressed in the antenna is very tightly linked to an autosomal gene controlling the interspecific difference in male behavioral response among Heliothis virescens and Heliothis subflexa. Moreover, single-cell recordings showed that species-specific spike-amplitude responses to individual pheromone components were also linked to the OR cluster (14). In O. nubilalis, five of the seven pheromone ORs are located within a large cluster on the Z chromosome (34).…”
Section: Significancementioning
confidence: 81%
“…The distance between the different loci is measured in centimorgans, and the LOD scores obtained for the ORs and the second peak are shown in boldface type. responses and most of the neurophysiological responses to pheromone components cosegregated with the autosomal OR cluster (14). The candidate genes in the Resp QTL region (Table 1) suggest that other factors affect the structure, function, or connectivity of the OSNs or other neurons in the antennal lobe or elsewhere in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, case studies indicating an absence of genetic coupling abound. For instance, in several species of moth, including the almond moth (6), adzuki borer moth (7), corn borer moth (8), and heliothine moths (9,10), it is quite clear that the female pheromone signal and male response are under separate genetic control. Similarly, male and female mating behaviors in Drosophila arizonensis and Drosophilia mojavenis have distinct genetic bases (11), as do pheromone production and response in the pine engraver beetle (12).…”
Section: Disentangling Coevolution and Genetic Couplingmentioning
confidence: 99%
“…However, the basic genetic architecture of prezygotic sexual isolation remains largely unexplored in most natural populations (4,5), and there is very little empirical evidence for tight genetic linkage between the emission and reception of a sensory signal (6)(7)(8)(9). Theoritical prediction and experimental studies assume that the "emission/reception coupling" depends on the inheritance of separate genes found on the same or on different chromosomes and linked with a high probability (linkage desequilibrium (10)(11)(12)(13)(14), whereas the "single-gene" hypothesis seems very unlikely (4), as the tissues involved in the emission and perception of sensory signals are usually different (15).…”
mentioning
confidence: 99%